Pediatric nursing consultation in the perspective of nurses from the family health strategy - Gasparino, Roberta Fernandes; Simonetti, Janete Pessuto [UNESP]; Tonete, Vera Lúcia Pamplona [UNESP] (My University, 2013)
Qualitative study that analyzed conceptions and experiences of nurses about the pediatric nursing consultation and its systematization in the Family Health Strategy. Semi-structured interviews were recorded with ten nurses from four cities of the countryside of São Paulo, in 2011. The interviews were analyzed according to the method of Thematic Content Analysis, based on current assumptions of the systematization of nursing care and the comprehensive child health care. Generally, nursing consultations, and specifically, pediatric ones were defined as the nurses’ activities that allows them to know the life/health story, current needs and prevent future problems, having recognized the importance of its implementation and systematization. The experiences reported the paucity and lack of systematization in the pediatric nursing consultation in the context studied. Processes of ongoing health education are necessary to ensure quality and completeness to children's health.

Investigación cualitativa que analizó concepciones y experiencias de enfermeros acerca de la enfermería pediátrica y su sistematización en la Estrategia Salud de la Familia. Las entrevistas semiestructuradas fueron grabadas con diez enfermeras de cuatro municipios del interior de São Paulo, Brasil, en 2011, analizadas según el método de Análisis Temático de Contenido, con base en supuestos actuales de la sistematización de la atención de enfermería y atención integral de la salud infantil. En general, la consulta de enfermería y, en específico la pediatría, fue definida como actividades que permite conocer la historia de las necesidades de la vida/salud y problemas actuales y futuros, siendo reconocida la importancia de su aplicación y sistematización. Las experiencias señalaron escasez y falta de consulta sistemática de enfermería pediátrica en el contexto estudiado. Procesos de educación continua en salud son necesarios para asegurar la calidad e integridad de la salud de niños.

Pesquisa qualitativa que analisou concepções e experiências de enfermeiros sobre consulta de enfermagem pediátrica e sua sistematização na Estratégia Saúde da Família. Entrevistas semiestruturadas foram gravadas com dez enfermeiras de quatro municípios do interior paulista, em 2011. Os depoimentos foram analisados segundo o método de Análise Temática de Conteúdo, com base em premissas atuais da sistematização da assistência de enfermagem e da assistência integral à saúde infantil. De modo geral, a consulta de enfermagem e, em específico, a pediátrica foram definidas como atividade do enfermeiro que possibilitam conhecer a história de vida/saúde e necessidades atuais e prevenir problemas futuros, sendo reconhecida a importância de sua realização e sistematização. As experiências relatadas apontaram a incipiência e a falta de sistematização da consulta de enfermagem pediátrica no contexto estudado. Processos de educação permanente em saúde revelaram-se necessários para assegurar qualidade e integralidade à saúde da criança.
Consulta de enfermería pediátrica en la perspectiva de enfermeros de la estrategia salud de la familia
Consultas de enfermagem pediátrica na perspectiva de enfermeiros da estratégia saúde da família
Keywords: Nursing; Family health program; Child health; Enfermería; Programa de salud familiar; Salud del niño; Enfermagem; Programa Saúde da Família; Saúde da criança